Development and Improvement of Business Process in the System "Bitrix 24" with the Use of Web Technologies - I. Ishmuradova, Izida; I. Makhmutov, Ilnur; A. Shakirova, Albina (International Journal of Engineering and Technology, 2018)
This article presents an analysis of the main functions of enterprise business management systems. The corporate portal Bitrix24 is considered which meets all the requirements of business process management systems. To ensure the integrity and availability of information, it is advisable to use the enterprise corporate portal within the Internet or Intranet as a platform for the BPM system. The use of the corporate portal is one of the modern trends in the management of the company's activities.The main principle of development of any enterprise is management built on business processes. In process management the key performance indicators of the enterprise are radically improved.Bitrix24 is the system for managing the company's internal information resource which unites people, processes and information in the company [1]. The software product is based on the Bitrix Framework. Technically the portal consists of a number of built-in modules, such as CRM, social networking, business processes, telephony, etc., and components.The article presents the development of a business process in this system. For the production company an improved business process for working with clients in CRM was designed and built. The business process was designed to automate routine operations and optimize the workflow of company employees.Â Â